2007
DOI: 10.1073/pnas.0708274104
|View full text |Cite
|
Sign up to set email alerts
|

Designer enediynes generate DNA breaks, interstrand cross-links, or both, with concomitant changes in the regulation of DNA damage responses

Abstract: The ability of the radiomimetic anticancer enediyne C-1027 to induce ataxia-telangiectasia mutated (ATM) and ATM and Rad3-related (ATR)-independent damage responses was discovered to reside in its unique ability to concurrently generate robust amounts of double-strand breaks (DSBs) and interstrand cross-links (ICLs) in cellular DNA. Furthermore, a single substitution to the chromophore's benzoxazolinate moiety shifted DNA damage to primarily ICLs and an ATR-but not ATM-dependent damage response. In contrast, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 22 publications
(56 reference statements)
3
76
1
Order By: Relevance
“…Preliminary investigation with S-ethyl and S-n-propyl analogs of AdoMet indeed demonstrated that NcsB1 can turnover 2,7-dihydroxy-5-methyl-1-naphthoic acid (8) into the corresponding 7-ethyl ether and 7-n-propyl ether, respectively, the identities of which have been confirmed by high resolution ESI-MS. Although these products were produced with significantly reduced efficiency relative to 9, the fact that NcsB1 is promiscuous toward AdoMet analogs presents yet another opportunity that potentially could be exploited to generate new NCS analogs with improved therapeutic properties (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary investigation with S-ethyl and S-n-propyl analogs of AdoMet indeed demonstrated that NcsB1 can turnover 2,7-dihydroxy-5-methyl-1-naphthoic acid (8) into the corresponding 7-ethyl ether and 7-n-propyl ether, respectively, the identities of which have been confirmed by high resolution ESI-MS. Although these products were produced with significantly reduced efficiency relative to 9, the fact that NcsB1 is promiscuous toward AdoMet analogs presents yet another opportunity that potentially could be exploited to generate new NCS analogs with improved therapeutic properties (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…All enediynes are comprised of an unsaturated core containing two acetylenic groups conjugated to a double bond or incipient double bond [13,27]. This conserved enediyne core is responsible for DNA damage and ultimately, cell death [10,21]. After the enediyne binds to DNA, the enediyne core, or warhead, undergoes electronic cyclization via a Bergman or Myers-Saito rearrangement affording a benzenoid diradical, which abstracts hydrogen atoms from the deoxyribose backbone of DNA [17,20,35].…”
Section: Introductionmentioning
confidence: 99%
“…PKSE uses a molecular logic that is distinct from all known PKS and FAS paradigms (17-25, 30 -36) and should serve as an inspiration for the continued search for other fatty acid and polyketide biosynthetic machinery. The characterization of a self-phosphopantetheinylating, functional enediyne PKS will be indispensable for combinatorial biosynthesis and genetic engineering in the quest to generate new enediynes and ultimately the discovery of new enediyne drugs with improved therapeutic index (48,49).…”
Section: Acp Domain Is Posttranslationally Modified By a C-terminal Pmentioning
confidence: 99%